Changes in the development of industrial space in the southern part of the 19th cadastral district of Cracow – Grzegórzki in the twentieth and twenty-first centuries on the example of Ludwik Zieleniewski’s machinery plant - Sobczyński, Marek (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The chapter presents the results of field research carried out in the industrialized area of the southern fragment of the 19th cadastral district of Cracow (Grzegórzki), in an urban block delimited by today’s streets: Grzegórzecka, Kotlarska and Zieleniewskiego and the Vistula embankment. Changes in the development of space will be shown, first in suburban areas, and from the first decade of the 20th century already in the urban area developed by the metal and machine industry plants of the brothers Ludwik and Edmund Zieleniewski, one of the oldest factory in this industry in Poland. To investigate the changes, a detailed field mapping of land use was used, made with the method proposed by the team of Karol Bromek (Bromek, Malinowska, Mydel 1971) on a 1:1 000 scale, carried out twice along 44 years period (summer–autumn 1975 and autumn 2019) (Sobczyński 1976). The mapping in the area was supplemented by the analysis of the cartographic material (topographic maps, aerial photos, orthophotomap) both from the pre-investment period (the end of the 19th century) and from the caesuras determined by successive stages of changes in the studied space in the period before the first mapping and between both mapping (1975–1999). From the end of the 19th century, there was an evolution in the use of the studied area of Cracow from agricultural, through industrial and transport to residential and recreational. The political transformations of Poland after 1989 were not conducive to the existence of the heavy machine industry and the plants were gradually closed down. The changes that took place in the study area are revolutionary, both as a transition at the beginning of the 20th century from rural to industrial space and a transformation at the beginning of the 21st century from post-industrial fallow land to an architecturally attractive and prestigious housing estate. The changes made affected the forms of spatial development and land use in the studied area, also in a revolutionary dimension.